PERBANDINGAN PEMEROLEHAN BAHASA INGGRIS SEBAGAI BAHASA ASING ANTARA PEMBELAJAR PEREMPUAN DAN PEMBELAJAR LAKI-LAKI MAHASISWA PROGRAM STUDI SASTRA INGGRIS UNIVERSITAS DEHASEN BENGKULU - Silvia Erlin Aditya; Djatmika Djatmika; Riyadi Santosa (Universitas Sebelas Maret, 2016)
The article talks about the process of acquiring English as a foreign language between male and female learners in English department, UNIVED. Data in the form of document were collected through students writing on descriptive and narrative texts from 28th September 2015 to 31th October 2015. The data were analysed through performance analysis in order to find out learners’ acquisition in composing descriptive and narrative text in English, to observe the process of acquiring English grammatical, to investigate learners’ language learning level through their acquisition on English word formation and to compare learners’ acquisition on foreign language based on their gender differences.The findings show that : (1)Description text is a genre that have been well mastered by learners of English in UNIVED (2)Learners have a low ability in acquiring English grammar with misformation and misapplied error category (3)Learners are found in Elementary level based on their acquisition on word format (4) Male learners exceed female learners in acquiring English. In general, the study shows that the acquisition of English as a Foreign Language of male and female learners in UNIVED is in low category. Keywords: descriptive, narrative, grammar, word format, foreign language acquisition.